Soils & Fertilizers for Master Gardeners: Urban Soils and their Management Issues - Amy L. Shober; Gurpal S. Toor (EDIS, 2009)
Revised! SL-276, a 3-page fact sheet by Amy L. Shober and Gurpal S. Toor, is part of the Soils and Fertilizers for Master Gardeners series. It describes the characteristics of urban soils and the associated management issues, specifically for soils in residential landscapes. Includes references. Published by the UF Soil and Water Science Department, January 2009.